1991
DOI: 10.2190/kwx7-y23t-6ytt-gdh0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizing Instructional Technologies and Educational Culture: Exploring Cognition and Metacognition in the Social Studies

Abstract: This research was initiated to examine instructional technologies and educational cultures in relation to identified cognitive and metacognitive strategies used in school tasks. The project involved activities from the social studies curricula that were presented through two new software programs intended to support the development of problem-solving and reasoning strategies—IDEA [Interactive Decision Envisioning Aid, Pea (76)] and Notecards (34)—and through instructional approaches based upon “cognitive appre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…(We bypass social studies because Thornburg and Pea [1991] have analyzed the synthesis of instructional technologies and educational culture in the context of social studies teaching from a perspective similar to our own. The curriculum areas that we choose to highlight are science, English, and mathematics.…”
Section: The Pedagogical Context Of Educational Computingmentioning
confidence: 99%
“…(We bypass social studies because Thornburg and Pea [1991] have analyzed the synthesis of instructional technologies and educational culture in the context of social studies teaching from a perspective similar to our own. The curriculum areas that we choose to highlight are science, English, and mathematics.…”
Section: The Pedagogical Context Of Educational Computingmentioning
confidence: 99%
“…The curricu lum areas that we choose to highlight are science, English, and mathe matics. (We bypass social studies because Thornburg and Pea [1991] have analyzed the synthesis of instructional technologies and educational cul ture in the context of social studies teaching from a perspective similar to our own. )…”
Section: The Pedagogical Context Of Educational Computingmentioning
confidence: 99%
“…The use of CAI software has been reported to increase cognitive domain, higher-order thinking skills as well. Thornburg and Pea [24] examined the effect of using two software programs-Interactive Decision Envisioning Aid (IDEA) and Notecards-to train high school students in cognitive strategy and metacognitive strategy. The results showed that after the training in learning strategies from the software program, the breadth and depth of the subjects' argumentation improved significantly when compared to their knowledge and abilities prior to the instruction.…”
Section: Computer Assisted Instruction and Learning Outcomesmentioning
confidence: 99%